A Qualitative Exploration of Intimate Partner Violence Among HIV/TB Coinfected Persons With Problematic Alcohol Use Participating in an Incentive-Based Alcohol/Medication Adherence Intervention in Uganda During COVID-19 - Miller, Amanda P. (Violence against women, 2025)
In Uganda, four in ten women report experiencing intimate partner violence (IPV) in the past year. Salient drivers of IPV in sub-Saharan Africa include stress related to household finances, alcohol use, and partner infidelity. We conducted 42 interviews with participants (n = 32) in the Drinkers' Intervention to Prevent Tuberculosis (DIPT) study which included economic incentives, and their partners (n = 10) to understand how participating in DIPT during COVID-19 lockdown restrictions impacted relationship dynamics in intimate partnerships. Our findings highlight the need to develop policies to address root causes of IPV and to ensure continuity of IPV services in future pandemics. Policy and programming recommendations based on study results are presented.